A Randomized Controlled Trial of Oral Versus Intravenous Administration of a Nonnarcotic Analgesia Protocol Following Pediatric Craniosynostosis Corrections on Nausea and Vomiting Rates. Issue 6 (September 2015) - Fearon, Jeffrey A.; Dimas, Vanessa; Ditthakasem, Kanlaya; Herbert, Morley A.
Abstract : Background: The authors' center uses a nonnarcotic postoperative regimen following craniosynostosis corrections. Despite opioid avoidance, the authors noted that some children still experienced nausea and vomiting following the oral administration of either acetaminophen or ibuprofen. This study sought to evaluate whether intravenous administration of these medications might reduce nausea and vomiting rates. Methods: A total of 50 children undergoing craniosynostosis corrections were prospectively randomized to a control group given only oral ibuprofen (10 mg/kg) and acetaminophen (15 mg/kg), or a treatment group given only intravenous ketorolac (0.5 mg/kg) and acetaminophen (15 mg/kg). All patients were assessed for postoperative nausea and vomiting by a blinded research nurse. Results: Twenty-eight patients randomized to the oral control group, and 22 to the intravenous treatment group. No statistically significant differences were identified between groups, including: age, weight, sex, before history of severe postoperative nausea and vomiting, or procedure. With similar anesthesia times there was significantly more vomiting episodes in the oral group (71% versus 41%). Using a multivariate logistic regression, controlling for age, weight and procedure, the odds ratio for vomiting in the oral control versus intravenous experimental groups was 3.61 (95% CI 1.11–1.76; P = 0.033), and for postoperative nausea was 14.0 (95% CI 1.40–71.69, P = 0.010). Conclusions: The authors found a significant reduction in nausea and vomiting among children randomized to receive intravenous medications. In addition, the intravenous delivery of medications has the theoretical advantage of insuring an effective full dose delivery. Based on these findings, our standard process is to preferentially manage all children following craniosynostosis corrections with intravenous nonnarcotics.